Intramolecular nitrone interrupted click reaction - Pothi, Tejas A.; Ramana, Chepuri V. (Organic Letters, 2024)
We document the intramolecular interception of a Cu-catalyzed azidoalkyne cycloaddition employing a suitably placed nitrone group, providing a simple route to the unprecedented spiro-polyheterocyclic scaffold. The reaction is comprised of a Cu-catalyzed [3 + 2]-cycloaddition of (2-azidoaryl)isatogen with a terminal alkyne and the intramolecular trapping of the transient Cu-triazolide intermediate with the isatogen, with a net formation of one C-C and two C-N bonds and the new heterocyclic ring being spiro-annulated.